Pituitary stalk interruption syndrome in 83 patients: novel HESX1 mutation and severe hormonal prognosis in malformative forms - Reynaud, R; Albarel, F; Saveanu, A; Kaffel, N; Castinetti, F; Lecomte, P; Brauner, R; Simonin, G; Gaudart, J; Carmona, E; Enjalbert, A; Barlier, A; et al. (European journal of endocrinology, 2011)
Pituitary stalk interruption syndrome (PSIS) is a particular entity in the population of patients with hypopituitarism. Only rare cases have a known genetic cause. i) To compare subgroups with or without extra-pituitary malformations (EPM) in a cohort of PSIS patients to identify predictive factors of evolution, ii) to determine the incidence of mutations of the known pituitary transcription factor genes in PSIS. Study design We analyzed features of 83 PSIS patients from 80 pedigrees and screened HESX1, LHX4, OTX2, and SOX3 genes. PSIS had a male predominance and was rarely familial (5%). Pituitary hypoplasia was observed only in the group with EPM. Multiple hormone deficits were observed significantly more often with versus without EPM (87.5 vs 69.5% respectively). Posterior pituitary location along the stalk was a significant protective factor regarding severity of hormonal phenotype. A novel HESX1 causative mutation was found in a consanguineous family, and two LHX4 mutations were present in familial PSIS. PSIS patients with EPM had a more severe hormonal disorder and pituitary imaging status, suggesting an antenatal origin. HESX1 or LHX4 mutations accounted for <5% of cases and were found in consanguineous or familial cases.